2009
DOI: 10.1183/09031936.00040509
|View full text |Cite
|
Sign up to set email alerts
|

Frequent nocturnal awakening in early life is associated with nonatopic asthma in children

Abstract: Sleep deprivation has become a common phenomenon of the Western world and is associated with a variety of medical problems in children. This retrospective longitudinal analysis of a community-based birth cohort was undertaken to determine whether frequent nocturnal awakening during early life was associated with the development of childhood asthma.2,398 children born to mothers recruited from the antenatal clinics of a single hospital in Perth, Australia during 1989-1991 were followed up at years 1, 2, 3, 6, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 56 publications
6
43
0
2
Order By: Relevance
“…Among studies that examined these conditions, only three detected significant risks, in two, associated with cats and/or dogs during early life [22,40], and in one, with rodents [14]. Frequent waking at night during the first 3 years of life, possibly related to respiratory infections, was associated with non-atopic asthma at ages 6 and 14 years [42]. …”
Section: Resultsmentioning
confidence: 99%
“…Among studies that examined these conditions, only three detected significant risks, in two, associated with cats and/or dogs during early life [22,40], and in one, with rodents [14]. Frequent waking at night during the first 3 years of life, possibly related to respiratory infections, was associated with non-atopic asthma at ages 6 and 14 years [42]. …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, an increased prevalence of sleep-related disorders, such as snoring, self-reported apnea, difficulty in inducing and maintaining sleep, and daytime sleepiness in asthmatic subjects has been reported [18,30,42]. In addition, other studies also have reported patients with SDB are more vulnerable to asthma [19,20]. All these studies, together with our cross-sectional study and meta-analysis, support the hypothesis that OSA and habitual snoring are independent risk factors for asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Not enough sleep in infants and children is associated with overweight/obesity and lower cognitive performance [101, 102], and sleep fragmentation increases the risk of asthma [103]. Sleep disorders are commonly comorbid with psychiatric conditions in children and adolescents [104], including attention deficit hyperactivity disorder, anxiety, depression, and autism spectrum disorders [105].…”
Section: What Can Go Wrong? Sleep Disturbances and Developmentmentioning
confidence: 99%